KEANEKARAGAMAN KEONG DI PULAU ENGGANO, BENGKULU UTARA - Heryanto Heryanto (BERITA BIOLOGI, 2017)
Research on the diversity of snails in Enggano, Central Bengkulu was held on 16 April 2015 to 5 May 2015 by taking three sampling sites that are north-western part of Enggano (Kampung Bendung at Desa Banjarsari and Desa Meok), the centralpart of Enggano (Desa  Malakoni) and the south-easternpart of Enggano (Desa Kaana). Sampling was conducted using purposive sampling while the analysis using graphical method and statistical cluster and t-test. This study found 722 specimens of snails which consists of 24 species from 17 families. Most of the snails found are in small size. Land snails in the forest dominates the north-easternpart as much as 88.2%. compared to  freshwater snails (11.8%). Terrestrial and freshwater snails share amount 50% each in the forest of the central, while terrestrial snails still dominate in the forest of south-eastern part (land snails: snail freshwater = 71.4%: 28.6% ). The existence of land snails and freshwater can not be separated from the state forests themselves besides the condition of the soil and surface water as a result of the topography of the island